Avaliação do modelo CROPGRO para detectar efeito da compactação do solo no crescimento e na produtividade da soja - Mulazzani, Rodrigo Pivoto (2020)
Soil compaction is an inherent phenomenon of the management of large-scale crops and can be associated to reduction on plant growth and yield. To know the effect of compaction on soil physical properties is insufficient to predict this association, because its occurrence depends on soil-plantatmosphere system interactions. The modelling of process is a strategy that allows to evaluate such interactions. The success of the models depends of the ability to integrate meteorological, phenological and soil elements to estimate stresses associated to poor supplying of plant demands. Stresses related to water deficit (water stress), oxygen deficit (oxygen stress) and excessive soil mechanical resistance (mechanical stress) suffer interference of soil physical properties affected by compaction. However, models that simulate plant growth and yield and that estimate mechanical stress are scarce. CROPGRO, a plant growth model of the DSSAT crop system model, addresses these requirements. Therefore, the objective of this study was to evaluate the performance of CROPGRO in detecting the association between soil compaction and soybean growth and yield. CROPGRO was evaluated in two studies. In the first one (manuscript 1), the sensitivity of the model to the effect of compaction on soybean performance was characterized. For this purpose, seven water deficit (WD) scenarios were combined with 12 soil compaction states (CS) scenarios in numerical experiments. The CROPGRO simulated soybean growth and yield without damage caused by an increase in EC when the DH occurred in the stages where the plant has low sensitivity to water restriction (beginning of the vegetative period and end of the reproductive period). Under water stress, CROPGRO indicates that the effect of EC is greater on yield than on leaf and root growth. In the second study (manuscript 2), the ability of CROPGRO to predict the effect of compaction on soybean growth and yield observed in a field experiment was evaluated. For this purpose, two soybean season crops (2016/17 and 2017/18) were conducted in three CS, represented by managements: compacted (CO), no-till (NT) and chieseling (CH). The CROPGRO estimates were near to the observed values of leaf area index and yield. However, root length density (RLD) estimates were not affected by managements while RLD observed were higher in CO and CH managements. This reveals the low sensitivity of the CROPGRO mechanical stress estimates to CS variation, especially when compared to the estimate of mechanical stress calculated from soil resistance to penetration (recently proposed by Moraes et al. (2018)). The results of the two studies indicate that the sensitivity of water, oxygen and mechanical stress estimates to changes in CS allows CROPGRO to make predictions about the association between compaction and soybean performance. However, there are opportunities for improvement in the estimate of mechanical stress by CROPGRO.